IMPLEMENTATION OF ISLAMIC CULTURE IN FORMING STUDENTS' MORALS BASED ON TEACHER EXAMPLE AT SMP N 7 BANDAR BARU, PIDIE JAYA DISTRICT - MK, Muhammad; Dhiauddin, Dhiauddin; Nazaruddin, Nazaruddin (PT. Hafasy Dwi Nawasena, 2025)
This study focuses on the problem: How is the role of teachers at State Junior High School 7 Bandar Baru in shaping students' morals through the application of Islamic culture, What forms of Islamic culture are developed at State Junior High School 7 Bandar Baru What are the supporting and inhibiting factors faced by teachers at State Junior High School 7 Bandar Baru in carrying out their role to shape students' morals through Islamic culture in schools. While this study aims to determine the role of teachers at State Junior High School 7 Bandar Baru in shaping students' morals through the application of Islamic culture, the forms of Islamic culture developed at State Junior High School 7 Bandar Baru, and what are the supporting and inhibiting factors faced by teachers at State Junior High School 7 Bandar Baru in carrying out their role to shape students' morals through Islamic culture in schools. This study uses a qualitative approach, which takes place at State Junior High School 7 Bandar Baru Pidie Jaya. The main source in qualitative research can be a person or an object. While the type of data is words in the form of spoken and written words and actions The data analysis techniques used include data reduction, data presentation, and the results of the research researchers found: The role of teachers in developing Islamic culture has been going well. Where teachers act as Teachers of Islamic culture, as participants in implementing Islamic culture, and as evaluators of Morals and Spirituality. While the forms of Islamic culture that have been developed so far are: Cultivate Congregational Prayer & Prayer, Ethics of Speaking with Teachers & Others, Diligently Reading Yasin, Prayer, and Wirid, Maintaining Private Parts with Islamic Clothing, Controlling Socializing According to Islamic Norms, Attending School on Time & Discipline, Do Greetings, Smiles, Saying Hello, and Shaking Hands, Noble Morals: Respect, Help, and Share, Cleanliness of the School Environment is Maintained Inspiring with Soft Speech, Prioritize Friendly and Fast Service, Train Yourself to Read Prayers and Short Verses, Routine Infaq and Millionaires of the Hereafter Every Friday Glorify Islamic Holidays Together. Meanwhile, the supporting and inhibiting factors for the implementation of Islamic school culture are: The supporting factors are the availability of adequate human resources and adequate facilities and infrastructure, while the inhibiting factors are the limited time and adequate facilities for character building. Student resistance to character education programs, especially in terms of discipline and responsibility. The existence of parents who are less active in implementing Islamic culture at home.